DEVELOPMENT OF STUDENTS' ARTISTIC SKILLS AND CREATIVE ABILITIES THROUGH THE EFFECTIVE MASTERING OF SCULPTURE (Intent Research Scientific Journal, 2023)
The article offers a method that can help students develop their artistic skills and creative abilities by effectively mastering sculpture. The study of sculpture explains that students will play a key role in creating ideas that allow them to feel, analyze, reason and express themselves in shapes.